2011
DOI: 10.1038/npp.2011.11
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Serotonin Transporter Gene-Linked Polymorphic Region and Stressful Life Events Predicts Cortisol Stress Response

Abstract: There has been significant controversy whether stressful life events (SLEs) experienced over the lifespan may elevate the risk of depression in individuals who are homozygous for the short (S) allele of the repeat length polymorphism (5-HTTLPR) in the regulatory region of the serotonin transporter gene (SLC6A4), compared with individuals homozygous for the long (L) allele. On the basis of the hypothesis that age may be a critical variable, by which such a gene-by-environment interaction may be present in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 47 publications
(56 reference statements)
3
75
3
Order By: Relevance
“…Individuals possessing two copies of the long allele with a low incidence of stressful life events (e.g., familial disruptions, health problems, interpersonal difficulties, etc.) had significantly greater cortisol output in response to stress than individuals with similar histories of stress with one or two copies of the short allele in a sample of 106 young adults [85]. However, for individuals that experienced high life stress, cortisol output was significantly higher in individuals possessing one or two copies of the short allele than homozygous long allele carriers.…”
Section: The Role Of the Hpa Axismentioning
confidence: 86%
See 1 more Smart Citation
“…Individuals possessing two copies of the long allele with a low incidence of stressful life events (e.g., familial disruptions, health problems, interpersonal difficulties, etc.) had significantly greater cortisol output in response to stress than individuals with similar histories of stress with one or two copies of the short allele in a sample of 106 young adults [85]. However, for individuals that experienced high life stress, cortisol output was significantly higher in individuals possessing one or two copies of the short allele than homozygous long allele carriers.…”
Section: The Role Of the Hpa Axismentioning
confidence: 86%
“…However, given the interaction between stressful life events and 5-HTTLPR, possessing short alleles might increase the likelihood that stressful life events would induce HPA axis hyperactivity. Indeed, the association between 5-HTTLPR and HPA axis activity appears to be dependent on history of life stress in young adults [85]. Individuals possessing two copies of the long allele with a low incidence of stressful life events (e.g., familial disruptions, health problems, interpersonal difficulties, etc.)…”
Section: The Role Of the Hpa Axismentioning
confidence: 99%
“…The transcriptional activity of the 5-HTT gene is significantly modulated by a length polymorphism in its promoter region, (termed the gene-linked polymorphic region; 5-HTTLPR) which produces two allelic forms of 5-HTTLPR: the long (L) allele and the short (S) allele, which is associated with lower transcriptional efficiency than the L allele (Lesch et al, 1996). While the 5-HTTLPR genotype has been clearly associated with individual differences in HPA axis activity (Barr et al, 2004;Gotlib et al, 2008;Jabbi et al, 2007;Mueller et al, 2011), studies of its effect on autonomic stress reactivity have produced conflicting results depending on parameters used. While in L allele carriers higher HR responses have been found (Williams et al, 2001(Williams et al, , 2008 to a mental stressor, another study found blood pressure (BP) to be unrelated to 5-HTTLPR genotype and HR to be greater only in women homozygous for the S allele (McCaffery et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, exposure to SLEs has been associated with increased cortisol release following psychological stressors in healthy adults with an exaggerated release in s-allele carrier, 74 an effect that is possibly moderated by age. 75 A baseline difference in serotonergic neurotransmission and in the connectivity and reactivity of brain regions that are important for emotion processing and stress reactivity conferred by the 5-HTTLPR could lead to early differences in emotional processing during exposure to stress and thus increase the vulnerability to psychiatric disorders. This gene-environment interaction may be particularly relevant if stressors are experienced during periods of heightened plasticity of brain regions that depend on serotonin neurotransmission.…”
Section: System Levelmentioning
confidence: 99%